2022
DOI: 10.1002/cssc.202102295
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ Generated CsPbBr3 Nanocrystals on O‐Defective WO3 for Photocatalytic CO2 Reduction

Abstract: Metal halide perovskite (MHP) nanocrystals (NCs) have shown promising application in photocatalytic CO2 reduction, but their activities are still largely restrained by severe charge recombination and narrow solar spectrum response. Assembly of heterojunctions can be beneficial to the charge separation in MHPs while the assembly process usually brings native interfacial defects, impeding efficient charge separation between two materials. Herein, an in‐situ generation strategy was developed to prepare CsPbBr3/WO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…As reported in our previous studies, inductively coupled plasma-mass spectrometry (ICP-MS) analysis indicated the presence of 0.31-0.40 wt% Pd and 0.012-0.042 wt% Cu in the porous polymer due to residual catalyst. [19,25] The formation of polymer networks was verified by cross-polarization/magic angle spinning (CP/MAS) 13 C NMR spectra and Fourier transform infrared (FT-IR) spectra (Figure S2-S5, Supporting Information). The 13 C NMR spectra showed peaks at approximately 120-140 ppm for all polymers, which could be assigned to sp 2 hybridized carbons.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in our previous studies, inductively coupled plasma-mass spectrometry (ICP-MS) analysis indicated the presence of 0.31-0.40 wt% Pd and 0.012-0.042 wt% Cu in the porous polymer due to residual catalyst. [19,25] The formation of polymer networks was verified by cross-polarization/magic angle spinning (CP/MAS) 13 C NMR spectra and Fourier transform infrared (FT-IR) spectra (Figure S2-S5, Supporting Information). The 13 C NMR spectra showed peaks at approximately 120-140 ppm for all polymers, which could be assigned to sp 2 hybridized carbons.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…However, compared to the large amount of research work done in the visible range with light wavelength of 420–550 nm, red light with low photoenergy has been rarely used for photocatalysis. To date, only a very limited number of photocatalysts have been reported for photocatalytic CO 2 reduction under light irradiation above 600 nm, such as Os(II)–Re(I) supramolecular complexes, [ 8 ] Ru complex/Ni–Al layered double hydroxide, [ 9 ] carbon dots/Bi 2 WO 6 , [ 10 ] ZnO/carbon dots, [ 11 ] Bi 2 O 3− x with oxygen vacancies, [ 12 ] CsPbBr 3 /WO 3 , [ 13 ] g‐C 3 N 4 /WO 3 ·H 2 O/Pd heterostructure, [ 14 ] etc. Among the studied photocatalysts, most are compositing materials, suffering from complicated preparation, low photocatalytic activity, and potential environmental issues resulting from the harmful heavy metals such as Cd, W, and Pb.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,7 ] In recent years, various kinds of perovskite photocatalysts have been developed, and they have exhibited great potential in photocatalysis. [ 8–31 ] However, the current perovskite photocatalytic systems generally have severe charge recombination. [ 22 ] The undesired charge recombination largely limits the transfer efficiency of the photogenerated charge carriers, which becomes the bottleneck in the development of the perovskite photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, embedding CsPbBr 3 into protective materials has to face many uncertainties such as reducing the absorption of light 32 or undesirability interface for inefficient charge transfer/separation. 33 Generally, the tighter the contact between the composites and the larger the area, the faster the photogenerated charge transport. 34 Moreover, reducing the size of each component of photocatalytic heterojunction materials has been demonstrated to be an effective strategy for maximizing carrier transport.…”
Section: Introductionmentioning
confidence: 99%